Peningkatan Literasi Melalui Program Study Tour di Sekolah Dasar - Ahmad Ahmad; Abdul Haris; Hermansyah Hermansyah; Wahyu Mulyadi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
The purpose of this service activity is motivated by the low literacy culture of students which can be seen from the low interest in reading of children in Kalampa Village, the low interest in reading is caused by several factors including family, environment, peers, and mobile phones. As an effort to improve children's literacy in Kalampa Village, a programme called Study Tour was designed with an integrated learning concept and outclass learning activities were carried out. The parties involved in this service activity are elementary school children in Kalampa Village, and students of PGMI Study Programmes of IAI Muhammadiyah Bima. In this service, the PAR (Participatory Action Research) method is used, which consists of several implementation phases, such as observation, planning, implementation, and evaluation. The results of the implementation of the study tour are very influential on increasing children's literacy and can foster children's learning motivation. through Study Tour activities children can express themselves through several games applied in learning. With intense guidance and an individualised approach, it has made a difference in improving children's literacy.